Life advices in patients with tracheostomy: Rational antibiotic use and cerebro-vascular prophylaxis-physiotherapy - Eylem Tuncay; Ozlem Yazicioglu Mocin; Sinem Gungor; Nezihe Ciftaslan Goksenoglu; Ilim Irmak; Cuneyt Salturk; Feyza Kargin; Huriye Berk Takir; Mustafa Ay; Veysel Garani Soylu; Emine Aksoy1; Gokay Gungor; et al. (Medicine Science, 2020)
Tracheostomy is life-saving procedure in critical care patients which require long-term mechanical ventilation (MV) and an alternative to endotracheal intubation.(1,2) The factors affecting the survival of tracheostomized patients are not clearly known. The aim of this study was to investigate the factors affecting intensive care unit (ICU) and long-term mortality in the tracheostomized patients due to respiratory failure. A retrospective observational cohort study was planned between January 2016-2019 in tertiary ICU. Each patient underwent percutaneous and surgical tracheostomy was included. Demographic characteristics, diagnoses, causes of tracheostomy, comorbidities, Charlson and APACHE 2 scores, culture antibiogram results, ICU day and mortality (1-3 and 12 months) were recorded. In the analysis of the data, appropriate statistical tests and analyzes were used. 115 of 3620 patients admitted to tertiary ICU and underwent percutaneous and surgical tracheostomy due to respiratory failure between January 2016-2019 were included. 75 (65%) of the patients were male and median age was 68±14 years. Hospital mortality was higher in the group with Acinetobacter baumannii growth (p=0.04). According to Kaplan-Meier survival analysis, long-term follow-up of Acinetobacter baumanii growth did not affect survival (p=0.938). Patients with cerebro-vascular accident (CVA) had lower survival in long-term follow-up (p [Med-Science 2020; 9(1.000): 1-5]